WORKPLACE HEALTH PROMOTION THROUGH ERGONOMIC EXERCISE AMONG INFORMAL PALM SUGAR WORKERS: A PRE-POST INTERVENTION STUDY - Ajeng Irawati; Aniek Puspitosari (Universitas Kusuma Husada Surakarta, 2026)
Background: Work fatigue is a common occupational health problem that reduces productivity, impairs work capacity, and increases the risk of occupational accidents, particularly among informal sector workers. Workplace health promotion strategies are needed to address this issue. Ergonomic exercise has emerged as a practical intervention to reduce physical fatigue and improve workers’ well-being. This study aimed to evaluate the effects of workplace health promotion through ergonomic exercises on reducing work fatigue among informal palm sugar workers.Methods: A quantitative pre-experimental study with a one-group pretest–posttest design was conducted among 60 informal palm sugar workers at Factory B, a branch production site of CV. Bangkit Jaya is located in Klaten Regency, Indonesia. Participants were recruited using purposive sampling. Work fatigue was assessed using the Industrial Fatigue Research Committee (IFRC) questionnaire before and after the intervention. Ergonomic exercise sessions were implemented 24 times over a 12-month period. Data were analyzed using the paired t-test.Results: Most participants were middle-aged (65.0%), female (57.1%), and had long working experience (83.3%). The mean work fatigue score decreased significantly from 65.40 before the intervention to 40.50 after the intervention, a reduction of 24.90 points. The paired t-test demonstrated a statistically significant reduction in work fatigue following the intervention (p < 0.001).Conclusion: Ergonomic exercise is an effective workplace health promotion strategy for reducing work fatigue among informal palm sugar workers. Incorporating ergonomic exercise into occupational health promotion programs may improve workers’ well-being, enhance productivity, and support sustainable health practices in the informal sector.